A estruturação das políticas LGBTI+ no Maranhão: As linhas, curvas e laços da engenharia política. - CANTANHEDE, Jaksoel Aroucha (2023)
This dissertation evaluates how the state policy against discrimination based on gender and sexuality has been oriented in recent years. Our study had as an analysis space the state of Maranhão. Thus, we have approached the context of the two drafts of the LGBTI+ State Plan, the last one with more rigor in its dimensions: its ethical and political reference; the determinants that conditioned its formulation; its principles of justice; its institutional and legal apparatus; its design, if it is consistent with the ends it aims to achieve. Besides, to unveil our object in its multiple determinations, and apprehend its complexity, we use the critical-dialectical method, as it allows us to understand the complex and contradictory totality that inserts our object in a society with deep patriarchal, historical, authoritarian, and exclusive roots. Therefore, we analyzed the socio-cultural and economic situation of the subjects of interest to capture the rationality of those involved in the formulation of the new Plan. Hence, we verify the main normative instruments that make up the legal apparatus of this new policy. In addition, to verify whether there is viability between objectives, means, and resources, we inquired if there is adequacy between the reality to be modified and the chosen form of governmental intervention. Thus, we approach qualitative data and sometimes quantitative data. We make use of technical procedures such as bibliographical review and documentary research to understand the establishment of this “issue” in the agenda of capitalist governments, after that, we focus on the formulation phase. The primary sources were documents published in the Official Gazette of the State (DOE), as well as journalistic articles, research produced by non-governmental organizations (NGOs), and other documents such as reports (or drafts) produced by interested subjects. In the end, our study allowed us to arrive at the following considerations: we noticed that LGBTI+ social movements played a prominent role in inserting the demands of its population in the state agenda and simultaneously their dialogue with party politics as well as contributed to the formulation of state government actions from 2004 onward. Additionally, we observed that different militants have joined the Administration, which has also, to a certain extent, driven the development of projects in favor of that population. Moreover, we detected that the new proposal of the plan under development favors the intersectoral model that radiates actions articulated by different government departments under the coordination of SEDIHPOP. However, the draft does not indicate tools to encourage the active adherence of these departments, so it disregards the interests that cross these sectors, either in terms of the managers' conceptions or in the training of the executors of these actions to facilitate the achievement of the objectives announced in the formulated draft. We also noted the absence of explicit control and monitoring mechanisms, although the intention to produce research and the monitoring of this policy is mentioned by civil society organizations, such as the Observatory of LGBTI+ State Policies, besides it, no other priority targets to be achieved were listed. In this manner, the new draft of the State Plan of Public Policies for the LGBTI+ Population in the state of Maranhão still demands improvements in its structure, since it contemplates purposes that must be accompanied at each stage for the next ten years by SEDIHPOP.